Kahoot! and EFL Learners' Confidence in A Vocabulary Classroom: A Correlative Study - pandu prasodjo; Glenn Ponto (English Education Study Program STKIP PGRI Pacitan, 2023)
The prevalence of English in recent years cannot be understated and this very sentiment rings true for almost every country worldwide. Among the various tools that are available for teaching, gamification tools of learning such as the application Kahoot! is seeing prominence in usage. Kahoot! promotes engagement and adds a fun factor in learning due to its interactive nature. Kahoot! also encourages competitiveness as it is a quiz-based application. A previous research found mentioned that Kahoot! decreases students’ confidence because of the competitiveness that stems from the quiz aspect of the application. The present study wishes to challenge the statement into test. The participants of this research are 36 first-year EFL students from a private university in Batam, Indonesia. The research conducted a correlational research design, providing quantitative data through the use of questionnaire and observation, which will be triangulated with a qualitative data gathered by the means of a guided interview. Spearman rule was used to analyse the correlation between the students’ ranking confidence and finding the correlation between both cycles. The study found that student’s confidence in learning vocabulary through the use of Kahoot! is initially positive and it grows with the passage of time.